Analgesia and patient comfort after enhanced recovery after surgery in uvulopalatopharyngoplasty: a randomised controlled pilot study - Fei Huang; Minxue Wang; Huixin Chen; Nan Cheng; Yanling Wang; Di Wu; Shaoli Zhou (BMC Anesthesiology, 2021)
Abstract Background Uvulopalatopharyngoplasty(UPPP) is the most prevalent surgical treatment of obstructive sleep apnea, but postoperative pharyngeal pain may affect patient comfort. The enhanced recovery after surgery pathway has been proved beneficial to many types of surgery but not to UPPP yet. The aim of this pilot study was to preliminarily standrize an enhanced recovery after surgery protocol for UPPP, to assess whether it has positive effects on reducing postoperative pharyngeal pain and improving patient comfort, and to test its feasibility for an international multicentre study. Methods This randomised controlled study analysed 116 patients with obstructive sleep apnoea (OSA) who were undergoing UPPP in a single tertiary care hospital. They were randomly divided according to treatment: the ERAS group (those who received ERAS treatment) and the control group (those who received traditional treatment). Ninety-five patients completed the assessment (ERAS group, 59 patients; control group, 36 patients). Pharyngeal pain and patient comfort were evaluated using a visual analogue scale (VAS) at 30 min and at 6, 12, 24 and 48 h after UPPP. Complications, hospitalisation duration, and hospital cost were recorded. Results The VAS scores for resting pain and swallowing pain were significantly lower in the ERAS group than those in the control group at 30 min and at 6, 12, 24 and 48 h after surgery. Patient comfort was improved in the ERAS group. The hospitalisation duration and cost were comparable between the groups. The incidence of complications showed an increasing trend in the ERAS group. Conclusion The ERAS protocol significantly relieved pharyngeal pain after UPPP and improved comfort in patients with OSA, which showed the prospect for an larger study. Meanwhile a potential increase of post-operative complications in the ERAS group should be noticed. Trial registration Chinese Clinical Trial Registry (23/09/2018, ChiCTR1800018537 )